2017
DOI: 10.1016/j.rehab.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training-induced modification in autonomic nervous system: An update for cardiac patients

Abstract: Patients with cardiovascular disease show autonomic dysfunction, including sympathetic activation and vagal withdrawal, which leads to fatal events. This review aims to place sympathovagal balance as an essential element to be considered in management for cardiovascular disease patients who benefit from a cardiac rehabilitation program. Many studies showed that exercise training, as non-pharmacologic treatment, plays an important role in enhancing sympathovagal balance and could normalize levels of markers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(100 citation statements)
references
References 141 publications
6
84
1
9
Order By: Relevance
“…Exercise also seems to positively effect synaptic plasticity and neuronal survival, 89,90 may decrease tumor necrosis factor (TNF) alpha which is correlated with neuronal damage post‐injury, 91 and has been associated with a reduction in free radical production post‐injury 92 . Exercise also positively influences autonomic dysfunction and cerebral blood flow, 93‐95 two factors felt to be disrupted post‐injury.…”
Section: Return To Learn and Return To Play (Rtl/rtp) Post‐mtbimentioning
confidence: 99%
“…Exercise also seems to positively effect synaptic plasticity and neuronal survival, 89,90 may decrease tumor necrosis factor (TNF) alpha which is correlated with neuronal damage post‐injury, 91 and has been associated with a reduction in free radical production post‐injury 92 . Exercise also positively influences autonomic dysfunction and cerebral blood flow, 93‐95 two factors felt to be disrupted post‐injury.…”
Section: Return To Learn and Return To Play (Rtl/rtp) Post‐mtbimentioning
confidence: 99%
“…The relationship between ANS dysfunction and PE, that we reported in our study, may suggest that treatment options associated with ANS dysfunction can improve PE. Regular exercise training may be quite helpful in improving the ANS dysfunction by increasing vagal modulation and decreasing sympathetic tone (Besnier et al, 2017). In this context, Kilinc et al reported an improvement in premature ejaculation parameters with moderate physical activity (Kilinc, Aydogmus, Yildiz, & Doluoglu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that autonomic disfunction is a striking characteristic in the physiopathologic path of cardiovascular diseases [3][4][5][6] . Because of that, measures that can revert or lessen these alterations deserve to be highlighted, among them is the aerobic training 19 and, as aforementioned, IMT. Indeed, many studies in this review pointed out the improvement of autonomic control with IMT, regardless of prescription or the manner of evaluating the ANS.…”
Section: Discussionmentioning
confidence: 99%